Gambaran Keterlibatan Orang Tua dalam Keterampilan Sosial Anak Penyandang Autisme - Filia Latuputty, Theofani; Wahyu Widayat, Iwan (CV RIFAINSTITUT, 2023)
The condition of children with autism generates obstacles in its development, especially when socializing. This condition makes parents face complex challenges in teaching social skills to children. Meanwhile, helping autistic children to learn social skills needs participation from their family. This study aims to describe the strategies used by parents to be involved in their autistic children’s social skills learning. This research is a qualitative study with data collection techniques using interviews, field notes, and collection of documents and artefacts. Data analysis is using Braun and Clark’s thematic analysis. The target participants in this study are mothers or fathers who have an autistic child in elementary school. Participants in this study are three mothers who has autistic child in elementary school. Based on the results, it can be concluded that parents use strategies to be involved as well as strategies to face the challenges while being involved. Parental involvement strategies that are found in this research are called Testing the Water and Collaborative Strategy. To face challenges in involvement, there are Finding Support and Avoidance of Stressor. Strategies used to be involved and face challenges of involvement needs to be adapted according to the needs and characteristics of children’s social skills in practice, also depends on the challenges faced by parents